Evaluation of the Health Data Management Practices and Related Factors among Saudi Arabian Health Professionals at Public Health Facilities in 2024 - Ahmed Mansour Alfuraydi,; Daidallah Abdulrahman M Al Otaibi,; Nada Alnuaseer,; Ibrahim Awad Saad Alahmari,; Youssef Ahmed Muhammad Surur,; Yaqob Yousef Omar Bakreem,; Majed Abdulrahman Abdulaziz Ahmed,; Omar Ahmed Maghfouri,; Ahmad Mohmaad Alshareef Rabee,; Laila Hazzaa Alsharif, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Health care practice depend on on evidence-based decisions and needs the use of quality health care data. Health management information system (HMIS) is among the core elements of health system building blocks. Information and data are essential to the process of making decisions about reforming the health system. Health workers still struggle with a lack of fundamental data management skills despite the vast sums of money spent on the creation of health information systems. Therefore, this study aims:To assess health data management practices and associated factors among health professionals in public facilities in Jeddah, Saudi Arabia. Method: A facility-based cross-sectional survey was conducted among 442 health professionals working in Jeddah, Saudi Arabia from January to Febraury 2024. Data were entered into Epi-Data V.4.6, and then it was exported to SPSS V.28 statistical software for processing and analysis. Bi-variable and multivariable logistic regression analyses were computed to see the association between health data management practiceand selected independent variables. The bi-variable logistic regression analysis model was used to identify candidate variables for multivariable regression, with a p value <0.2 fitted into the multivariable logistic regression analysis model; a p value less than 0.05 and an adjusted OR (AOR) with a 95% CI were used to declare statistical significance associated with the dependent variable. Results: The prevalence of good health data management practices among health professionals was found to be 51.1%, with a 95% CI (45.9 to 55.7). In this study, received training on health data management (AOR=1.82, 95% CI (1.06 to 3.13)), used appropriate technology (AOR=1.78, 95% CI (1.09 to 2.91)) and competency (AOR=6.62, 95% CI (4.06 to 10.80)) were positively associated with health data management practice among health professionals. Conclusion and recommendations: Nearly half of health professionals had poor health data management practices. All healthcare facilities should have appropriate and functional health data management technology.